Expanding Research Capacity in Sub-Saharan Africa Through Informatics, Bioinformatics, and Data Science Training Programs in Mali - Shaffer, Jeffrey G.; Mather, Frances J.; Wele, Mamadou; Li, Jian; Tangara, Cheick Oumar; Kassogue, Yaya; Srivastav, Sudesh K.; Thiero, Oumar; Diakite, Mahamadou; Sangare, Modibo; Dabitao, Djeneba; Toure, Mahamoudou; et al. (Frontiers in Genetics, 2019)
Bioinformatics and data science research has boundless potential across Africa due to its high levels of genetic diversity and disproportionate burden of infectious diseases, including malaria, tuberculosis, HIV/AIDS, Ebola virus disease, and Lassa fever. This work lays out an incremental training approach for engaging underserved populations in bioinformatics and data science research at the University of Sciences, Techniques and Technologies of Bamako, Mali (USTTB). Two informatics training programs sponsored by the Fogarty International Center were carried out at USTTB between 1999 and 2011. Coupled with these efforts and capacity from a large epidemiological cohort study in Mali, a bioinformatics and data science training program was launched at USTTB in 2017 as part of the Human Heredity and Health in Africa (H3Africa) initiative. The informatics training programs included 12 long-term trainees and 53 short-term trainees. Eight of the 12 (67%) long-term trainees completed master’s degrees at foreign institutions as part of their training. Prior to the training, these trainees published 2 first or second authorship and 8 third or higher authorship manuscripts at rates of 0.40 and 0.10 per year, respectively. Following the training, these rates increased to 55 first or second authorship and 99 third or higher authorship manuscripts at rates of 0.70 and 1.23 per year, respectively (p<.001). The bioinformatics and data science training program at USTTB commenced in 2017 focusing on student, faculty, and curriculum tiers of enhancement. The program’s sustainable measures included institutional support for core elements, university tuition and fees, resource sharing with ongoing research projects and companion training programs, increased student and faculty publications, and increased research proposal submissions. Long-term, incremental processes are necessary for engaging historically underserved communities in bioinformatics and data science research. The multi-tiered enhancement approach described here provides a platform for generating bioinformatics technicians, teachers, researchers, and program managers. Increased literature on bioinformatics and data science training approaches and progress would provide a framework for establishing benchmarks on the topic.